High Correctness Mobile Money Authentication System - Osman, Fouad (International Journal of Psychosocial Rehabilitation, 2020)
Mobile money is a mobile embedded system that is used for money deposit, money withdrawer, items purchase, bills payment, airtime and internet recharges. The current mobile money authentication system uses personal identification number (PIN) that is feeble, vulnerable to shoulder surfers and susceptible to mobile money attackers. To solve this flaws of mobile money authentication system and to establish high correctness mobile money authentication system. A new mobile money authentication system is studied. Key aspects for high correctness of mobile money authentication system is to correctly accept real mobile money users and to properly reject mobile money non-users. To correctly evaluate the mobile money users by the authentication system, mobile money system should have functions to identify and verify the users and functions to authorize the transactions of the money. To detect the mobile money user, a unique identity number is registered during mobile money user enrolment. To verify the identity of the user and authorize transactions, iris biometric authentication system is proposed and added in to the mobile money system. Iris biometric system is the most secured, robustness and reliable authentication system. It is real time verification system that cannot change with age and have minimum accuracy error rate. Users can easily accept Iris biometric system as mobile money authentication system because mobile camera can take the eye- iris images. In this paper a high correctness mobile money authentication system is propose that is based on iris biometric system and unique user ID number. The paper also outlines qualitative approach, interviewed number of mobile money users from their point of view and perspectives about the proposed iris system. Results show that most of the interviewee are highly welcome security strength to mobile money, particularly iris authentication system. Finally the paper discuss future research opportunities and limitations of the study.